2015
DOI: 10.1186/1745-6215-16-1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from recruiting socioeconomically disadvantaged smokers into a pilot randomized controlled trial to explore the role of Exercise Assisted Reduction then Stop (EARS) smoking

Abstract: BackgroundResearch is needed on what influences recruitment to smoking reduction trials, and how to increase their reach. The present study aimed to i) assess the feasibility of recruiting a disadvantaged population, ii) examine the effects of recruitment methods on participant characteristics, iii) identify resource requirements for different recruitment methods, and iv) to qualitatively assess the acceptability of recruitment. This was done as part of a pilot two-arm trial of the effectiveness of a novel beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
208
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(212 citation statements)
references
References 31 publications
(34 reference statements)
1
208
1
2
Order By: Relevance
“…Effect sizes, SEs, P –values and the main conclusions drawn by the authors were extracted from the papers for both primary and main secondary outcomes. Studies are generally only powered to detect estimated differences between experimental and control groups for the primary outcome, and thus Bayes factors may be particularly useful for secondary analyses 15, 16. Concerns have been raised previously regarding the interpretation of non‐significant findings for sensitivity analyses 15, 16.…”
Section: Methodsmentioning
confidence: 99%
“…Effect sizes, SEs, P –values and the main conclusions drawn by the authors were extracted from the papers for both primary and main secondary outcomes. Studies are generally only powered to detect estimated differences between experimental and control groups for the primary outcome, and thus Bayes factors may be particularly useful for secondary analyses 15, 16. Concerns have been raised previously regarding the interpretation of non‐significant findings for sensitivity analyses 15, 16.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, others have reported that recruitment facilitators include engagement with the target population when developing the intervention and preparing participant information about the study; 106 a personalised and culturally sensitive approach to participants; 99,107 designing recruitment processes that are aimed towards clearly highlighting to potential participants the beneficial outcomes of taking part and addressing any barriers or perceived negative outcomes; 108 providing research and implementation support by providing a dedicated research team contact; 109 minimising the workload for participants by adapting trial processes so they are in line with usual ways of working at the site; 109 providing financial or other incentives; 29 and good communication and expressions of appreciation to site facilitators and participants. 108,109 Although some have suggested the value of using technology such as internet-based questionnaires 110 and the use of video to provide trial information [111][112][113] to improve recruitment, a recent systematic review 98 concluded that their effect is not clear.…”
Section: Strategies To Optimise Recruitment and Retentionmentioning
confidence: 99%
“…A systematic review of trial site performance showed longer delays to trial sites opening in high-income countries (median time = 250 days; 188–266) [9] than in our trial. Our study was, however, multi-jurisdictional requiring different ethical approvals and one regulatory obligation [42–44].…”
Section: Discussionmentioning
confidence: 64%
“…Planning for clinical trial site initiation typically begins before protocol development with the conduct of feasibility assessments for their suitability and readiness in respective settings [9]. As part of the planning process, investigators need to consider building a qualified implementation team, assessing the local environment and complex dynamics of the target community, infrastructure needs and the potential to conduct and complete the trial within the proposed timelines.…”
Section: Introductionmentioning
confidence: 99%